2022
DOI: 10.3389/fmolb.2022.831382
|View full text |Cite
|
Sign up to set email alerts
|

KRAS Mutation in Rare Tumors: A Landscape Analysis of 3453 Chinese Patients

Abstract: KRAS is the most commonly mutated oncogene in human cancers. Targeted therapy and immunotherapy for this gene have made remarkable progress in recent years. However, comprehensive molecular landscape analysis of KRAS in rare tumors is lacking. Retrospective analysis was performed on clinical samples from patients with rare tumors collected between September 2015 and September 2021, using hybrid-capture-based next-generation sequencing for genomic profiling and immunohistochemistry assay for PD-L1. Of the 3,453… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…G12D (60%) is the dominant mutant subtype of KRAS in this study, and we still found that the numbers of patients who survived over one year in wild- type KRAS group were greater than those in the KRAS mutation (n=3 vs n=0). Evidence exists that KRAS- mutant cancers with the G12C subtype, instead of the G12D subtype, was associated with higher TMB and PD-L1 positivity rate compared with wild-type KRAS ( 32 ). Novel inhibitors targeting KRAS ( G12C ), such as AMG510 (sotorasib) and MRTX849 (adagrasib), have displayed promising results in preclinical and clinical trials, due to the covalent inhibition of cysteine and high GTPase activity of KRAS ( G12C ) ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…G12D (60%) is the dominant mutant subtype of KRAS in this study, and we still found that the numbers of patients who survived over one year in wild- type KRAS group were greater than those in the KRAS mutation (n=3 vs n=0). Evidence exists that KRAS- mutant cancers with the G12C subtype, instead of the G12D subtype, was associated with higher TMB and PD-L1 positivity rate compared with wild-type KRAS ( 32 ). Novel inhibitors targeting KRAS ( G12C ), such as AMG510 (sotorasib) and MRTX849 (adagrasib), have displayed promising results in preclinical and clinical trials, due to the covalent inhibition of cysteine and high GTPase activity of KRAS ( G12C ) ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically in NSCLC, KRAS G12C is the most common mutant subtype, accounting for roughly 45% of all KRAS mutations, followed by G12V and G12D [ 18 ]. Apart from the common tumor types, the landscape of the KRAS mutation in rare tumors is investigated, with an overall mutation rate of 8.7%; and G12D and G12V, along with G13D, are the most common subtypes [ 19 ]. The KRAS mutation frequency and subtype proportion in common cancers are summarized in Table 1 .…”
Section: Kras Mutations In Cancersmentioning
confidence: 99%
“…A previous study in Chinese NSCLC patients reported a prevalence of 10.7% and 4.6% in overall KRAS mutation and G12C, respectively. We depicted the first KRAS mutation landscape of rare tumors in a large Chinese rare tumor population and observed an overall prevalence of 8.7% of KRAS mutation, concentrated on G12D, G12V, and G13D (Wang et al , 2022a ). The G12C mutation was found in 0.6% of the population.…”
Section: Potential Therapeutic Targets For Rare Tumors In Chinamentioning
confidence: 99%
“…The G12C mutation was found in 0.6% of the population. However, a higher rate of G12C mutations was observed in sarcomatoid carcinoma of the lung (SARCL) and clear cell ovarian cancer (CCOV), with a prevalence of more than 5% (Wang et al , 2022a ).…”
Section: Potential Therapeutic Targets For Rare Tumors In Chinamentioning
confidence: 99%